Analysis of CV. Yan's Jaya Financial Statements Fiscal Reconciliation in 2023 on Calculating Income Tax Payable - Agustini, Sri; Kamaliyah, Fithrah (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
In Indonesia, the self-assessment tax system requires taxpayers, including corporations, to calculate, report, and pay their own taxes based on applicable regulations. However, differences between commercial and fiscal financial statements often lead to miscalculations in determining taxable income. Fiscal reconciliation is necessary to align financial reporting with tax regulations, ensuring compliance and accurate corporate income tax calculations. The aim of this research was to ascertain the taxable income generated by CV. Yan's Jaya by comparing commercial and fiscal financial statements. Descriptive quantitative methods were employed in this study, with the analysis based on data from the Annual Report. Data collection was carried out at CV. Yan's Jaya by collecting financial statement data in the company year, which became the research sample, namely the company. The data was collected by CV Yan's Jaya by using the documentation method. The company's calculation of taxable income is under scrutiny in relation to accounting standards and tax laws. Despite conducting fiscal reconciliation on the commercial income statement, mistakes have been identified that are affecting the accurate assessment of Corporate Income Tax owed.